Analisis Beban Kerja Mental Menggunakan Metode Nasa – TLX Pada Divisi Human Capital Services Officer - Prastiyo, Muhammad Rizky; Sari, Rianita Puspa (Fakultas Teknik Universitas Tulang Bawang, 2024)
TTA is a mining company with a significant role played by the Human Capital Services Officer division. Employees are faced with a heavy mental workload. Intense industry competition demands improved performance in a short time with minimal errors. This study aims to analyze the mental workload in the Human Capital Services Officer division using the Nasa-TLX method. Employees work 5 days a week for 8 hours per day, but all employees in the Human Capital Services Officer division work beyond regular hours without overtime pay or shift rotation. The study utilizes the Nasa-TLX method to analyze the mental workload in the division. Out of 17 employees surveyed, 5 experienced excessive mental workload, while 12 had an optimal workload. Factors affecting the mental workload include Mental Demand, Temporal Demand, Frustration Level, and Performance Level. This analysis provides a better understanding and information that can be used to enhance user experience and work efficiency. Thus, this research provides important insights in managing workload within the Human Capital Services Officer division of PT.TTA Keywords: Employee Working Hours, Mental Workload, Nasa-TLX Method